A general equilibrium analysis of the economic impact of the post-2006 EU regulation in the services sector - Javier Barbero; Manol Bengyuzov; Martin Aarøe Christensen; Andrea Conte; Simone Salotti; Aleksei Trofimov (European Commission, Joint Research Centre (JRC), 2022)
This study uses both econometric and modelling techniques to quantify the macroeconomic impact of regulatory reforms removing barriers in the European Single Market for services that have taken place in the European Union between 2006 and 2017. It also provides scenario analyses of the impact of a number of hypothetical additional reforms aimed at further reducing regulatory restrictions. The results of the modelling simulations indicate that the regulatory reforms implemented between 2006 and 2017 will result in discounted cumulative gains of 2.1% of GDP by the year 2027. Furthermore, ambitious additional reforms from 2017 onwards would generate an additional growth potential of 2.5% of GDP by 2027. Combining the realised and potential gains would result in a cumulative gain in GDP of 4.65% and a rise in employment of more than 300,000 full time equivalents by 2027. More conservative hypotheses on the additional reforms from 2017 onwards would lead to a GDP cumulative gain of 3.22% by 2027.
Keywords: C68; R13; 330; Services regulation; general equilibrium modelling; Single Market; economic growth